Indigenous Australian Students’ Participation Rates in Higher Education: Exploring the Role of Universities - Pechenkina, Ekaterina; Kowal, Emma; Paradies, Yin (The Australian Journal of Indigenous Education, 2011)
Indigenous Australians are underrepresented and considerably disadvantaged within the Australian system of higher education. The various measures taken by Australian universities over the past decades have produced varying levels of success in increasing Indigenous participation and completion rates. In order to continue improving Indigenous Australian participation in higher education, it is important to understand the current patterns of participation and factors within universities that are associated with participation and success. In this article we analyse higher education student and staff statistics available from the Department of Education, Employment and Workplace Relations (DEEWR) and information sourced from the web sites of 40 Australian universities to examine correlations between various Indigenous student support mechanisms and Indigenous students' higher education participation rates. Our results indicate that there is a dual system of Indigenous higher education, with one group of universities excelling at attracting Indigenous students, and a different group of universities demonstrating high Indigenous student completion rates. We argue that challenges remain in determining how to increase commencements at universities with high Indigenous completion rates without compromising entrance requirements or further diluting the level of student support, and how to increase completion rates at universities with higher numbers of Indigenous students.